Pemalsuan Akta Autentik Sebagai Aspek Pidana Notaris - M. Jamil (BESTUUR, 2019)
The notary is known as a respected official in accordance with the mandate of the law. In Article 1 paragraph 1 of the Amended UUJN, it is stated that a Notary Public is authorized to make an authentic deed and has other authorities as referred to in this Law or based on other laws. Sometimes the labeling of the word "honorable" carried by a notary is injured by irresponsible notaries. many persons who do not think long will be the result of what has been done. The increasing number of notaries and the complexity of the problems faced by a notary public there are also notaries who are entangled with legal cases related to authentic deed forgery. The State of Indonesia is a state of law, in a state of law all people are treated equally before the law, this also applies to the profession of Notary. Notaries can be convicted if they meet the criminal elements contained in Article 263 paragraph (1) and Article 264 paragraph (1) of the Criminal Code. In this study, the author conducted a juridical-normative analysis based on literature study. Keywords: Authentic Deed, Criminal Aspects, Notary Public.